The evolutionary and ecological potential of yeast hybrids. (October 2022) - Stelkens, Rike; Bendixsen, Devin P
Abstract : Recent findings in yeast genetics and genomics have advanced our understanding of the evolutionary potential unlocked by hybridization, especially in the genus Saccharomyces. We now have a clearer picture of the prevalence of yeast hybrids in the environment, their ecological and evolutionary history, and the genetic mechanisms driving (and constraining) their adaptation. Here, we describe how the instability of hybrid genomes determines fitness across large evolutionary scales, highlight new hybrid strain engineering techniques, and review tools for comparative hybrid genome analysis. The recent push to take yeast research back 'into the wild' has resulted in new genomic and ecological resources. These provide an arena for quantitative genetics and allow us to investigate the architecture of complex traits and mechanisms of adaptation to rapidly changing environments. The vast genetic diversity of hybrid populations can yield insights beyond those possible with isogenic lines. Hybrids offer a limitless supply of genetic variation that can be tapped for industrial strain improvement but also, combined with experimental evolution, can be used to predict population responses to future climate change — a fundamental task for biologists.